Structure and evidence of validity of the Spanish version of the Psychosocial Values Questionnaire (QVP-24) - Alonso, Daniela (2018)
This article presents evidence of validity and reliability of the Spanish version of the Psychosocial Values Questionnaire (QVP-24) by Pereira, Camino and Da Costa (2004). This instrument is based on a theoretical approach that combines sociological and psychological perspectives of the social values analysis. Two similar samples of citizens from Córdoba (AR) between 18 and 70 years old were surveyed. With data from the first sample, an exploratory factor analysis was conducted, while data from the second sample was used to obtain confirmatory evidence of the instrument’s structure. The results yielded four dimensions, which showed adequate adjustment and internal consistency coefficients. In addition, evidence of concurrent validity was obtained through the correlation of these dimensions with a right wing authoritarianism (RWA) scale (Etchezahar, Cervone, Biglieri, Quattrocchi, & Prado- Gascó, 2011). In conclusion, the validity of this instrument and its importance in the field of social and political psychology are confirmed.